2019
DOI: 10.1200/jco.18.00636
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib With Neoadjuvant Chemotherapy for Breast Cancer Might Worsen Outcomes Differentially by COX-2 Expression and ER Status: Exploratory Analysis of the REMAGUS02 Trial

Abstract: PURPOSE The overexpression of cyclooxygenase 2 (COX-2) gene, also known as prostaglandin-endoperoxide synthase 2 ( PTGS2), occurs in breast cancer, but whether it affects response to anticox drugs remains unclear. We investigated the relationships between PTGS2 expression, celecoxib use during neoadjuvant chemotherapy (NAC), and both event-free survival (EFS) and overall survival (OS). MATERIALS AND METHODS We analyzed a cohort of 156 patients with human epidermal growth factor receptor 2 –negative breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Preclinical and clinical studies showed that nonsteroidal anti-inflammatory drugs (NSAIDs) have chemopreventive effects on several cancers including BC [68][69][70], and exert anti-tumor activities, and in particular ketorolac when administrated in the peri-operative setting [65,71]. However, their routine use as adjuvant treatment in BC is still inconsistent and not yet recommended [72][73][74][75][76][77][78][79]. Of interest, mounting evidence indicate that inflammation may promote acquired endocrine resistance and more aggressive progression or ER + BC [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies showed that nonsteroidal anti-inflammatory drugs (NSAIDs) have chemopreventive effects on several cancers including BC [68][69][70], and exert anti-tumor activities, and in particular ketorolac when administrated in the peri-operative setting [65,71]. However, their routine use as adjuvant treatment in BC is still inconsistent and not yet recommended [72][73][74][75][76][77][78][79]. Of interest, mounting evidence indicate that inflammation may promote acquired endocrine resistance and more aggressive progression or ER + BC [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…In a REMAGUS02 trial, a phase II randomized controlled trial, celecoxib combined with sequential neoadjuvant chemotherapy (NAC) (epirubicin + cyclophosphamide followed by docetaxel) shows poorer event-free survival and distant relapse-free survival and OS than the NAC group, particularly the prostaglandin-endoperoxide synthase 2 (PTGS2; also called COX-2)-low or estrogen receptor-negative group. 191 The effects of celecoxib on breast cancer depend on the expression of PTGS2 and estrogen receptor status, as validated in PTGS2-low/high breast cancer cell lines. In vitro data show that adding celecoxib promotes cancer cell survival only in PTGS2-low cell lines.…”
Section: Conventional Drugs With New Use: Candidate For Tme-targetingmentioning
confidence: 99%
“…In vitro data show that adding celecoxib promotes cancer cell survival only in PTGS2-low cell lines. 191 Another noteworthy phenomenon is that celecoxib may induce COX-2 expression in lung cancer cells. Expressed COX-2 protein could reportedly be transferred by exosomes to other cells such as monocytes and THP-1 cells, thereby increasing PGE 2 and VEGF production.…”
Section: Conventional Drugs With New Use: Candidate For Tme-targetingmentioning
confidence: 99%
“…A recent exploratory analysis of the REMAGUS02 trial reported survival detriment with COX2-inhibitor celecoxib use in PTGS2 (COX2)-low breast cancer patients, but not in PTGS2-high patients, who received neoadjuvant docetaxel chemotherapy. 19 There was significant interaction between celecoxib use and PTGS2 expression, suggesting that both the deleterious effect of celecoxib use with chemotherapy and the therapeutic benefit of COX inhibition in PTGS2-high patients are at play. Several other prospective trials also reported a lack of benefit or association with poorer outcomes with COX2-inhibitor use in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 95%